The cost of worrying about an epidemic: Ebola concern and cognitive function in the US - Christian Apenbrink (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Do emotional responses to the spread of an infectious disease affect the quality of economic decision-making? In the context of an episode of heightened public concern about Ebola in the US in October 2014, I document that worrying about the possibility of an epidemic can impair cognitive function. My analysis relies on data from cognitive tests administered as part of a wave of survey interviews by a large US panel study, which I combine with measures of local concern about Ebola based on internet search volume. For identification, I exploit temporal and spatial variation in Ebola concern caused by the emergence of four cases of Ebola that were diagnosed in the US. Using proximity to the US cases as an instrumental variable, I show that the local level of Ebola concern individuals are exposed to at the time and place of the interview reduces their scores on the cognitive test. In additional analyses, I find no indication of fear-induced selection effects that could plausibly explain these results. Moreover, proximity to subsequent Ebola locations is unrelated to test scores for interviews conducted before the emergence of the first US case. My findings indicate that emotional responses to epidemics can entail a temporary cognitive cost even for individuals for whom the actual health risk never materializes.
Keywords: D91; 330; Worry; Fear; Emotions; Ebola; Epidemics; Cognitive Function